Effect of cabergoline and metformin combination therapy in the treatment of infertile women with symptomatic endometrioma: comparison with cabergoline alone - Akter, Asma; Banu, Jesmine; Islam, Jahirul; Ishrat, Shakeela; Renu, Rafikunnahar; Chowdhury, Tanzina Iven; Laila, Rawnok; Lasker, Nastaran; Islam, Tahmida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometrioma is a prevalent manifestation of endometriosis and a common cause of infertility in women of reproductive age. This study aimed to evaluate the effectiveness of cabergoline alone versus in combination with metformin in infertile women with symptomatic endometrioma. Methods: This randomized controlled trial was conducted in the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from July 2022 to June 2023. This study included 50 women with clinically and sonologically diagnosed cases of endometrioma and dysmenorrhea attending the Reproductive Endocrinology and Infertility outpatient Department. Participants were assigned to two treatment groups: Group A (Cabergoline with metformin) and Group B (Cabergoline alone). Results: Baseline demographic and clinical characteristics were comparable between the groups. At 3 months, both groups showed significant reductions in pain scores (Group A: 5.38±2.52; Group B: 4.86±1.52) and endometrioma size (Group A: 1.11±0.75 cm; Group B: 0.72±1.10 cm), with slightly higher reductions in Group A. However, the differences were not statistically significant (p>0.05). Endometrioma size reduction was more pronounced in Group A (mean difference: 1.11 cm vs. 0.72 cm; effect size 1.26 vs. 0.75). Side effects were mild and comparable in both groups, with no statistically significant differences. Conclusions: This study showed that both treatment regimens significantly improved pain and reduced endometrioma size, with no significant difference in outcomes between the groups. The combination of cabergoline and metformin may offer a slight advantage in reducing endometrioma size and improving fertility outcomes.